Evangelical Environmentalists? Evidence from Brazil. - Smith, Amy Erica; Veldman, Robin Globus (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2020)
While scholarship on the relationship between religions and environmental attitudes has been inconclusive, evangelical Protestants present an exception: they consistently report less environmental concern than other groups. However, prior studies have largely been conducted in the United States. Following a recent "contextual" turn, we revisit the assumption that universal cognitive and doctrinal factors drive the previously documented negative association between evangelicalism and environmental concern. Leveraging qualitative fieldwork, nationally representative surveys, and a survey experiment from Brazil, we find that evangelical and Pentecostal affiliation and church attendance are not associated with reduced environmental concern; that members of these groups simultaneously embrace otherworldly beliefs and advocate for this‐worldly solutions to environmental problems; and that being primed to consider divine intervention increased support for environmental protection. Even in a tradition emphasizing orthodoxy, doctrine appears not to exert a universal influence, a finding we suggest results from different issue frames in the United States and Brazil.